Cardioprotective Effect of Rheum turkestanicum Against Doxorubicin-Induced Toxicity in Rats - Azar Hosseini; Azar Hosseini; Mohammad-Kazem Safari; Arezoo Rajabian; Samaneh Boroumand-Noughabi; Ali H. Eid; Yusra Al Dhaheri; Eric Gumpricht; Amirhossein Sahebkar; Amirhossein Sahebkar; Amirhossein Sahebkar; Amirhossein Sahebkar (Frontiers Media S.A., 2022)
Background: Doxorubicin as an anti-cancer drug causes cardiotoxicity, limiting its tolerability and use. The mechanism of toxicity is due to free radical production and cardiomyocytes injury. This research evaluated Rheum turkestanicum (R.turkestanicum) extract against doxorubicin cardiotoxicity due to its considerable in vitro antioxidant activity.Methods: Male Wistar rats received 2.5 mg/kg doxorubicin intraperitoneally every other day for 2 weeks to create an accumulative dose. R. turkestanicum was administrated at a dose of 100 and 300 mg/kg intraperitoneally from the second week for 7 days. On the 15th day, the animals were anesthetized and blood was collected from cardiac tissue for evaluation of alanine aminotransferase (ALT), cardiac muscle creatinine kinase (CK-MB), troponin T (cTn-T), lactate dehydrogenase (LDH), and B-type natriuretic peptide brain natriuretic peptide. A cardiac homogenate was also collected to determine superoxide dismutase (SOD), catalase Catalase Activity, malondialdehyde (MDA), and thiols. Histopathology was also performed.Results: Doxorubicin increased all cardiac enzymes and malondialdehyde, correlating with a reduction in SOD, catalase, and thiols. Histopathology revealed extracellular edema, moderate congestion, and hemorrhage of foci. In contrast, administration of R. turkestanicum ameliorated these doxorubicin-induced pathophysiological changes.Conclusion: This study revealed that the extract ameliorated doxorubicin-induced cardiac toxicity via modulation of oxidative stress-related pathways. Liquid chromatography-mass spectrometry analysis of R. turkestanicum indicated several components with potent pharmacological properties.